Effect of laser treatment on postural control parameters in patients with chronic nonspecific low back pain: a randomized placebo-controlled trial - Taradaj,J. (2019)
The management of nonspecific lumbar pain (NSLP) using laser irradiation remains controversial. A systematic review of recently published studies indicates that the effects of laser therapy are commonly assessed using only imperfect methods in terms of measurement error. The main objective of this study was to assess static postural stability using an objective tool in patients with chronic NSLP after laser irradiation at different doses and wavelengths. In total, 68 patients were included in the laser sessions and were randomly assigned into four groups: high-intensity laser therapy at 1064 nm and 60 J/cm2 for 10 min (HILT), sham (HILT placebo), low-level laser therapy at 785 nm and 8 J/cm2 for 8 min (LLLT), and sham (LLLT placebo). In addition, all patients were supplemented with physical exercises (standard stabilization training). To assess postural stability, a double-plate stabilometric platform was used. All measurements were performed pre- and post-laser sessions (three weeks) and at follow-up time points (one and three months). Laser procedures led to more balanced posture stability in patients, although these positive changes were significant mainly for short-term observation (after 4-week therapy). In the follow-up analysis, the parameters were gradually impaired. Kruskal-Wallis analysis of variance (ANOVA) for independent variables did not show any difference between the studied groups. Low- and high-intensity laser therapy does not lead to a significant improvement in postural sway in patients with NSLP compared with standard stabilization training based on short- and long-term observations.